2008
DOI: 10.1007/s00128-008-9601-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Border Response of Moss, Hypnum cupressiforme Hedw., to Atmospheric Deposition in Southern Bulgaria and Northeastern Greece

Abstract: This study aimed at first cross-border mapping of 10 heavy metals and toxic elements accumulation in moss Hypnum cupressiforme reflecting wet and dry atmospheric deposition in Southern Bulgaria and Northeastern Greece. It is a part of the European moss survey 2005/2006 including first Greek results. Data obtained from 66 sites, covering 20,000 km(2), showed different deposition patterns particularly for As, Cd, Cr and Pb. The determined concentrations (ICP-AES), revealed no serious pollution by airborne heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…This distinction was performed in order to separately study the case of Skouries and to understand the impact that the mining activities have on the area. The results of the current study are in agreement with the data obtained from a previous moss biomonitoring study held in Northeastern Greece, close to the Bulgarian boarders [55]. A more detailed discussion of the measured elemental concentrations may be found in [56].…”
Section: Elemental Concentrations In Mossessupporting
confidence: 91%
“…This distinction was performed in order to separately study the case of Skouries and to understand the impact that the mining activities have on the area. The results of the current study are in agreement with the data obtained from a previous moss biomonitoring study held in Northeastern Greece, close to the Bulgarian boarders [55]. A more detailed discussion of the measured elemental concentrations may be found in [56].…”
Section: Elemental Concentrations In Mossessupporting
confidence: 91%
“…Similar studies were carried out in 2000 by the Vysehrad Group countries—Hungary, Czech Republic, Poland and Slovakia (Suchara et al 2007). Biomonitoring studies utilising mosses include also the local cases, such as a pilot study comparing the sorption properties of various moss species in Latvia 1993 (Ceburnis et al 1997); determination of the concentrations of heavy metals in moss samples collected around the industrial facilities in Estonia, in 1992, 1997 and 2002, carried out to estimate the distribution of the deposition of these metals in the vicinity of their sources (Liiv and Kaasik 2004); studies in the Romanian city of Baia Mare hosting several copper, zinc and lead works (Culicov et al 2002); studies in Bulgaria and the European part of Turkey (Coşkun et al 2009); studies in Greece (Yurukova et al 2009) and studies in Belgrade, where moss samples collected in autumn 2004 were analysed using the neutron activation analysis (INAA) to determine 36 elements and to indicate their main sources—fuel burning for energy production and vehicle emissions (Aničić et al 2007). Determination of heavy metals accumulated in mosses were also carried out in Vietnam (Nguyen-Viet et al 2007), Pakistan (Rahman et al 2000) and in the South Ural (Smirnov et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Other cross-border moss data in this region from Southern Bulgaria and Northeastern Greece, and join moss network in Southeastern Bulgaria and European Turkey were already published(4,20). Comparing the last published median values in European mosses(5)and the median concentrations of Bulgarian mosses, was found that the Pb, Fe, V, Ni and Cu values in Hypnum cupressiforme were higher (2-fold to 4-fold), than median values for European mosses.…”
mentioning
confidence: 90%